Contemporary Indonesian Film; Spirits of Reform and ghosts from the past - van Heeren, Katinka (Verhandelingen van het Koninklĳk Instituut voor Taal-, Land- en Volkenkunde, 2012)
This highly informative book explores the world of Post-Soeharto Indonesian audio-visual media in the exiting era of Reform. From a multidisciplinary approach it considers a wide variety of issues such as mainstream and alternative film practices, ceremonial and independent film festivals, film piracy, history and horror, documentary, television soaps, and Islamic films, as well as censorship from the state and street. Through the perspective of discourses on, and practices of film production, distribution, and exhibition, this book gives a detailed insight into current issues of Indonesia’s social and political situation, where Islam, secular realities, and ghosts on and off screen, mingle or clash. Dr. Katinka van Heeren was born on 7 January 1973 in Jakarta Indonesia. She has been a student of Indonesian Languages and Cultures since 1995. Over the years she built up a specialization in Javanese culture, Indonesian Islam, and contemporary audio-visual media. In 2000 she obtained her Masters degree at the University of Leiden with a thesis on media, identity politics and socio-political influences of New Order rule in Indonesian culture in the analysis of two Indonesian films. From 2001 to 2005 she was member of the Indonesian Mediations research project. This project was part of a larger Dutch KNAW research project of Indonesia in Transition. In June 2009 she obtained her doctorate. Between 2001 and 2010 she has organized several film screenings in the Netherlands and Indonesia, as well as took part at different film festivals as a member of the jury. She is affiliated to ASEAC, which bi-annually organizes the Southeast Asian Cinemas Conference, and KSI, a group of Indonesian scholars who study recent developments in Indonesian audio-visual media